Teaching English for Intensive Program: A Need Analysis - Irra Wahidiyati; Desi Wijayanti Ma'rufah; Winanti (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
In UIN Prof. K.H. Saifuddin Zuhri, most students, who had taken an English Proficiency Test at the beginning of the academic year to recognize the students' English proficiency, did not achieve a passing grade (450 points) of the test. This condition drives the institution to improve the student's English proficiency through the intensive language program that the Language Development Unit organizes. The research uses a descriptive study to analyze the data from the questionnaire, in which each item is analyzed individually. Fifty students' questionnaire answers and the interview of ten lecturers are grouped and analyzed to identify their real needs. The data is evaluated descriptively based on the percentage of student responses. The study results show that the language skills needed in intensive English courses are listening, structure and written expression, and reading. Most of the lecturers said that the students lacked grammar. Therefore, students need listening, structure and written expression materials, and reading skills—the essential skills to improve our structure and writing. Also, vocabulary and grammar are the aspects of the language that should be improved in the intensive English class. When developing the material, the target needs analysis should be considered, including language skills, language aspects, English learning objectives, and the time commitment of the Intensive English language program.